Proton Pump Inhibitors and Fractures in Adults: A Critical Appraisal and Review of the Literature - Silvia Irina Briganti; Anda Mihaela Naciu; Gaia Tabacco; Roberto Cesareo; Nicola Napoli; Pierpaolo Trimboli; Marco Castellana; Silvia Manfrini; Andrea Palermo (International Journal of Endocrinology)
Despite the large number of patients worldwide being on proton pump inhibitors (PPIs) for acid-related gastrointestinal disorders, uncertainty remains over their long-term safety. Particularly, the potential side effects of these drugs on bone health have been evaluated in the last years. The purpose of our narrative review is to gather and discuss results of clinical studies focusing on the interactions between PPIs and fracture risk. Data generated mainly from nested case-control studies and meta-analysis suggest that long-term/high-dose PPIs users are characterized by an increased risk of fragility fractures, mainly hip fractures. However, in these studies, the PPIs-induced bone impairment is often not adjusted for different confounding variables that could potentially affect bone health, and exposure to PPIs was reported using medical prescriptions without adherence evaluation. The mechanisms of the PPI-related bone damage are still unclear, but impaired micronutrients absorption, hypergastrinemia, and increased secretion of histamine may play a role. Clinicians should pay attention when prescribing PPIs to subjects with a preexistent high risk of fractures and consider antiosteoporotic drugs to manage this additive effect on the bone. However, further studies are needed to clarify PPIs action on the bone.